1992
DOI: 10.1287/mnsc.38.10.1371
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Loyalty and Switching with an Application to the Automobile Market

Abstract: A brand switching model that considers the choices: previous choice, current choice, and substitute choice, if the current choice were not available, is developed and estimated. An important assumption of the model is that the market consists of two types of consumers: "Loyals" and "Shoppers." The model provides estimates for: (1) the proportion of Loyals in a submarket, and (2) the success of each submarket in capturing Shoppers. We illustrate how the model can be used to characterize the competitive structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
0
31
0
5
Order By: Relevance
“…Recently, models which simultaneously group consumers and brands have been proposed. McCarthy, Kannan, Chandrasekharan & Wright (1992) is a typical example of this line of research. Service marketing research, in particular that relating to professional services, has revealed the importance of the relationship between the buyer and the seller, relative to characteristics of either the buyer or seller in isolation (Gronroos, 1990;Sharma, 1991).…”
Section: Auditor Change Literaturementioning
confidence: 99%
“…Recently, models which simultaneously group consumers and brands have been proposed. McCarthy, Kannan, Chandrasekharan & Wright (1992) is a typical example of this line of research. Service marketing research, in particular that relating to professional services, has revealed the importance of the relationship between the buyer and the seller, relative to characteristics of either the buyer or seller in isolation (Gronroos, 1990;Sharma, 1991).…”
Section: Auditor Change Literaturementioning
confidence: 99%
“…Brand names facilitate this process by providing instant recognition which in turn makes favorable associations between brand names and quality [17]. In subsequent empirical studies, each of the 48 brands studied displayed highly significant brand-specific parameters at the 0.01 level [8] with repeat purchases for Chrysler leading Ford, General Motors and foreign manufacturers across both a national and a state sample [9].…”
Section: Consumer Expectationsmentioning
confidence: 93%
“…Secondly, we integrate various aspects of the car buying experience from both the consumer's and the producer's perspective in contrast with the existing literature has been confined to either one or the other. The consumer position has been analyzed in terms of leasing [7], brand loyalty [8], brand name [9], price responsiveness to taste [10], socio-demographic profile [11], and fuel economy [12]. The producer position has been examined from the standpoint of consumer rebates [13], lemons [14] and consumer loans [15].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to be the case in the market for cars ( [26]; [27]). It has been shown that self-image related to car ownership of the specific brand is especially important in the case of luxury car purchases ( [65]; [66]).…”
Section: Dynamics In the Market For Consumer Productsmentioning
confidence: 94%
“…It implies that consumers assess the attractiveness of each product based on its market share, which can be interpreted as brand recognition. Brand is an important determinant of purchase of cars [26]. As technological standards of cars improve over time, segmenting the luxury cars based on their technological categories becomes increasingly difficult, causing the perceived image of cars to play more important role in purchasing decisions of consumers [27].…”
Section: Introductionmentioning
confidence: 99%